Union of Comoros : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper assesses the main fiscal trends of the Comorian economy over 2005-15. It highlights continued difficulties in the fiscal performance of and the outlook for Comoros as a result of systemic challenges in revenue administration and public financial management. In particular, there is a structural imbalance between domestic resource mobilization and current spending, especially on public wages and salaries, leaving little scope for domestically financed capital spending, which is essential for economic growth and social development. This fiscal imbalance is more pronounced than in similar sub-Saharan African countries, even after taking into account sizable one-off budget grants that benefited the Comorian economy.